Teaching and Assessment Strategies for Psychomotor Skills in Dental Education: Scoping Review - Ossa, Gustavo; Jelicic-Alcalde, Maira; Ramos-Salinas, Elizabet; Vidal, Felipe; Bäumle, Rosario (Spanish Journal of Medical Education, 2025)
Introduction: The dental profession requires high manual skills to perform precise procedures in the oral cavity. These skills, known as psychomotor skills, integrate cognitive and motor abilities that allow the student to adapt and interact effectively with their environment. Since these skills are primarily developed through constant practice, rigorous training before clinical contact with patients is essential. Simulation, as an educational tool, has gained particular importance due to its ability to replicate real clinical conditions, facilitating the development of both technical and cognitive skills. Methods: A search was conducted in the PubMed, Scopus, and Web of Science databases, following the PRISMA-ScR, JBI protocol, and utilizing the AI software Rayyan. Results: The main teaching strategies include low-fidelity simulation, screen simulators, and virtual resources. Regarding assessment, these strategies are categorized into diagnosis, training, and self-assessment. The key features of these tools include benefits for students in terms of motor skill development, safety, and self-criticism, as well as reducing the teaching load in assessment, improving educational planning, and providing useful feedback. Conclusions: The strategies analyzed are effective for simultaneously developing and/or measuring multiple skills or knowledge. However, the lack of information on their impact on meaningful learning limits their implementation. Future studies need to explore their effectiveness in greater detail, outlining application protocols to facilitate the comparison of strategies and optimize their use in dental education.